Personality Associations With Smartphone and Internet Use Disorder: A Comparison Study Including Links to Impulsivity and Social Anxiety - Jessica Peterka-Bonetta; Cornelia Sindermann; Jon D. Elhai; Jon D. Elhai; Christian Montag (Frontiers Media S.A., 2019)
The present work aims to replicate findings linking specific personality traits with Internet and Smartphone Use Disorder (IUD/SUD). Specifically, earlier research demonstrated that tendencies toward IUD and SUD are associated with high Neuroticism and both low Conscientiousness and low Agreeableness, while IUD (but not SUD) tendencies are negatively related to Extraversion and SUD (but not IUD) tendencies are negatively associated with Openness (1). In the aftermath of the replication crisis in psychology and related disciplines, it has become increasingly important to replicate findings in psychological research. Therefore, we revisited this earlier study by investigating (i) a sample from different countries and (ii) using different questionnaires to assess IUD, SUD and the Five Factor Model of Personality than the earlier work by Lachmann et al. (1). By applying such a design, we believe that replicating results from this earlier study hints toward generalizable associations being (largely) independent from that sample's specific cultural background and instrumentation. Importantly (iii) we used a larger sample consisting of N = 773 in the present study to have higher statistical power to observe the initially reported associations. Additionally, we investigated the role of impulsivity and social anxiety on IUD/SUD, further illuminating the nature of these potential new disorders. Indeed, we were able to reaffirm the aforementioned correlation patterns between personality and IUD/SUD in the present work to a large extent, with low Conscientiousness and high Neuroticism being most robustly associated with higher IUD/SUD. Furthermore, social anxiety and impulsivity showed positive correlations with IUD and SUD, as expected.